Private Education Provision and Public Finance : The Netherlands - Patrinos, Harry Anthony (Taylor and Francis, 2013)
One of the key features of the Dutch education system is freedom of education – freedom to establish schools and organize teaching. Almost 70% of schools in the Netherlands are administered by private school boards, and all schools are government funded equally. This allows school choice. Using an instrument to identify private school attendance, it is shown that the Dutch system promotes academic performance. The instrumental variable results show that private school attendance is associated with higher test scores. Private school size effects on math, reading, and science achievement are 0.19, 0.31, and 0.21, respectively.